A Novel Solid‐state Electrochemiluminescent Enantioselective Sensor for Ascorbic Acid and Isoascorbic Acid. Issue 2 (25th August 2016) - Zhu, Shu; Lin, Xia; Wang, Qinghong; Xia, Qiao; Ran, Peiyao; Fu, Yingzi
Abstract: A novel, stable, solid‐state and stereoselective electrochemiluminescence (ECL) sensor has been designed to enantioselectively discriminate ascorbic acid (AA) and isoascorbic acid (IAA) by immobilizing Ru(bpy)3 2+ (Ru), thiolated β‐cyclodextrin (β‐CD‐SH) and gold/platinum hybrid nanoparticles supported on multiwalled carbon nanotube/silica coaxial nanocables (GP‐CSCN) on glassy carbon electrode. All chemical compounds could be immobilized on the surface of electrode stably through nafion film, and high stereoselectivity could be introduced to the sensor via the synergistic effects of the β‐CD‐SH and GP‐CSCN nanomaterials. When the developed sensor interacted with AA and IAA, obvious difference of ECL intensities was observed, and a larger intensity was obtained from AA, which indicated that this strategy could be employed to enantioselectively recognize AA and IAA. As a result, ECL technique might act as a promising method for recognition of chiral compounds. Abstract :